Investigation, Formulation and Development of an Open GUI for the Touchscreen Smartphone - Sooknanan, Daniel Jovan; Joshi, Ajay (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The use of touchscreens in handheld mobile devices, including mobile phones, PDA’s, media players and tablet PC’s, has rapidly increased in recent times. One of the most important aspects of these devices is the software which comprises the Graphical User Interface (GUI). This paper is centered on designing and implementing an open source GUI for a touchscreen smartphone, with the overall intent being to verify that the use of open source development tools can reduce the cost of production and by extension the cost of smartphones on the market. The methodology adopted to achieve successful completion of this research included comprehensive background research into existing GUI design theory and mobile usability studies, and applying these findings to the design of an open source GUI, within the constraints of an Embedded Linux target platform. The major outcomes of this study include the successful formulation and design of a hierarchical, touchscreen GUI suitable for a smartphone, as well as successful development and target-specific implementation of this GUI on an Embedded Linux, ARM-based platform, functioning as a hypothetical smartphone. After successful implementation of the GUI, it can be said that the adoption of an open source philosophy in the design of a smartphone GUI can reduce overall cost.